Introducción al problema de la erosión litoral en urabá (sector arboletes-turbo) costa caribe colombiana (2004)
Shoreline retreat has been the net dominant historical trend along the 145 km-length littoral between Arboletes and Turbo (Southern Caribbean of Colombia). For the last four decades, there were identified in this littoral shoreline retreats of about 50-100m in several places (Uveros, Damaquiel, Zapata, Turbo) and a maximun of 1.6 km in the Punta Rey-Arboletes area, where land losses were of 4.5 km2, at exceptional rates of 40m/year. The synthesis of the available information suggest that the general "susceptibility" to erosion between Arboletes and Turbo could be related primarily to relative sea level rise, associated to tectonic movements as well as to the effects of mud diapirism and hydroisostacy. In the more critical areas (Arboletes, Turbo), the natural erosive trends were accelerated by anthropic actions, including river diversion (Turbo), beach mining, and inadequate (or total absense) practices for controlling residual and natural waters. Up to August 2000, there were invested about $ Col 10.000 billions in 155 engineering defences (groins, sea walls and rip-rap which totalize 6.2 km of total length and a volume of materials of 37.000 m3). With few exceptions, groins have not been successful and are now part of the problem, accelerating shore erosion along the adyacent sectors. In the short term, the littoral erosion between Arboletes and Turbo is caused both by marine and by subaerial factors. It is facilitated by the poor lithological strengths of cliffs and marine terraces, mainly composed of highly fractured and weathered claystones and mudstones (with stratification and weakeness planes dipping toward sea) and nonconsolidated, easily liquefacted, fine sediments; both conditions facilitate the occurrence of rocks falls, slides and mud flows that result in high figures of cliff retreat (3 to 4m), specially during the first 15 days of the summer-winter transition (April) and in high waves periods. The case of the littoral erosion between Arboletes and Turbo illustrates well how the natural erosive trends of an area can be accelerated by human interventions and the urgent need for coordinating efforts to cope with littoral land losses.